Bromodomain Protein BRD4 Is Required for Estrogen Receptor-Dependent Enhancer Activation and Gene Transcription - Nagarajan, S; Hossan, T; Alawi, M; Najafova, Z; Indenbirken, D; Bedi, U; Taipaleenmäki, H; Ben-Batalla, I; Scheller, M; Loges, S; Knapp, S; Hesse, E; et al. (Elsevier, 2014)
The estrogen receptor α (ERα) controls cell proliferation and tumorigenesis by recruiting various cofactors to estrogen response elements (EREs) to control gene transcription. A deeper understanding of these transcriptional mechanisms may uncover therapeutic targets for ERα-dependent cancers. We show that BRD4 regulates ERα-induced gene expression by affecting elongation-associated phosphorylationof RNA polymerase II (RNAPII) and histone H2Bmonoubiquitination. Consistently, BRD4 activity isrequired for proliferation of ER+ breast and endometrial cancer cells and uterine growth in mice. Genome-wide studies revealed an enrichment of BRD4 on transcriptional start sites of active genes and a requirement of BRD4 for H2B monoubiquitination in the transcribed region of estrogen-responsive genes. Importantly, we demonstrate that BRD4 occupancy on distal EREs enriched for H3K27ac is required for recruitment and elongation of RNAPII on EREs and the production of ERα-dependent enhancer RNAs. These results uncover BRD4 as a central regulator of ERα function and potential therapeutic target. © 2014 The Authors.